2007
DOI: 10.1182/blood-2007-05-092189
|View full text |Cite
|
Sign up to set email alerts
|

Friend retrovirus infection of myeloid dendritic cells impairs maturation, prolongs contact to naïve T cells, and favors expansion of regulatory T cells

Abstract: IntroductionDendritic cells (DCs) are the most potent antigen-presenting cells (APCs) of the immune system, and they are pivotal in the initiation of immune responses against viruses. 1 However, a number of viruses are able to infect DCs, and several recent studies have investigated the effect of such infections on the biology of DCs. Although only very few studies report enhanced or unchanged functions of DCs after viral infection, most viruses seem to impair functional properties of DCs (for review, see Poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…24 It is therefore possible that enhanced activation of DCs by cellular ICs may not only favor the activation of antiviral CTLs, but also may tip the balance of CD4 ϩ Th/Treg cells toward Treg differentiation. Also underlining a possible role for DCs in counteracting the appearance of induced Tregs, Balkow et al 46 reported that, in the FV model, DC precursors are infected and do not fully mature into DCs, which is crucial for expansion of FoxP3 ϩ Tregs. Should this also occur in FrCas E -infected/ nontreated mice, it is likely that limitation of viral spread on the administration of 667 would also help to preserve DC function to generate an efficient antiviral response.…”
Section: Discussionmentioning
confidence: 99%
“…24 It is therefore possible that enhanced activation of DCs by cellular ICs may not only favor the activation of antiviral CTLs, but also may tip the balance of CD4 ϩ Th/Treg cells toward Treg differentiation. Also underlining a possible role for DCs in counteracting the appearance of induced Tregs, Balkow et al 46 reported that, in the FV model, DC precursors are infected and do not fully mature into DCs, which is crucial for expansion of FoxP3 ϩ Tregs. Should this also occur in FrCas E -infected/ nontreated mice, it is likely that limitation of viral spread on the administration of 667 would also help to preserve DC function to generate an efficient antiviral response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously shown that FV-infected DC can expand the population of Foxp3 ϩ cells in vitro upon presentation of antigen to naive T cells. 44 Because FV-infected DC were also found in spleens of infected mice, 44 it remains possible that virus-infected DC induce the proliferation of Treg at the site of infection. However, our current results show that CD8 ϩ T cells play a vital role in Treg expansion (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FV also infects MHC II-expressing cells, such as B cells and macrophages (11,20,26), and bone marrow precursors of MHC II-expressing macrophages and dendritic cells (1,2). However, FV replicates mainly in nucleated erythroid precursors, which do not express MHC class II molecules and would not therefore be directly recognized by FV-specific CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%